Twenty-five women who shaped the early modern Holy Roman Empire : past and present struggles over the symbolic order - Keller, Katrin; Heise, Bernard (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Challenging the conception that only men shaped the Holy Roman Empire, this book provides students and general readers with biographies of preachers, nuns, princesses, businesswomen, artists scientists, writers and social movers who exercised agency in the Holy Roman Empire. Who was Maria Theresa Paradis, and have you ever heard of Empress Eleonora Magdalena? Numerous women achieved prominence or made important contributions to the life of the early modern Holy Roman Empire, but they are only gradually being rediscovered. Generations of historians had assumed that princely women were essentially limited to childbearing, or townswomen to running the household. And although it took a long time for higher education to become attainable to women, they also made their voices heard in the sciences, arts and religion. A closer look indeed reveals that the history of the Empire was also a history of the interaction of men and women and a history of women's self-empowerment. This book offers a biographical perspective on that past, as well as a fascinating panorama of women who left their mark on the Holy Roman Empire. This book is the perfect introduction to anyone wishing to broaden their knowledge of women's history, the Holy Roman Empire and early modern Europe"--
Caritas (Barbara) Pirckheimer (1467-1532) : the learned nun -- Katharina Zell (1497/98-1562) : a woman who preached -- Maria of Hungary (1505-1558) : on behalf of the dynasty -- Elisabeth of Brunswick-Calenberg (1510-1558) : a princess as reformer -- Anna of Saxony (1532-1585) : of princely domains and good medicines -- Archduchess Maria of Inner Austria (1551-1608) : how a mother shapes her children -- Polyxena of Lobkowicz (1566-1642) : between Bohemia and Spain -- Anna of Brandenburg (1576-1625) : how Prussia came to Brandenburg -- Maria Magdalena Haidenbucher (1576-1650) : abbess in troubled times -- atharina Regina von Greiffenberg (1633-1694) : the poet in exile -- Maria Sybilla Merian (1647-1717) : science and painting -- Glikl bas Judah Leib (1647?-1724) : the experiences of a Jewish businesswoman -- Empress Eleonora Magdalena (1655-1720) : how to care for your siblings -- Maria Aurora von Königsmarck (1662-1728) : the mistress in the imperial abbey -- Erdmuthe Benigna of Reuss-Ebersdorf (1670-1732) : women and the Pietist movement -- Maria Margaretha Kirch (1670-1720) : the arduous journey to the sciences -- Luise Adelgunde Gottsched (1713-1762) : more than the woman at his side -- Dorothea Erxleben (1715-1762) : a medical doctor prevails -- Empress Maria Theresa (1717-1780) : the heiress -- Anna Dorothea Therbusch (1721-1782) : from innkeeper to court painter -- Anna Barbara Gignoux (1725-1796) : how to defend a calico factory -- Sophie von La Roche (1730-1807) : a life as a female author -- Amalie Gallitzin (1748-1806) : philosophy, religion, and conviviality -- Maria Theresia Paradis (1759-1824) : the blind pianist -- Henriette Herz (1764-1847) : a salon in Berlin.
Keywords: Women -- Holy Roman Empire -- Biography; Holy Roman Empire -- Civilization; HISTORY / General; HISTORY / Europe / General; HISTORY / Europe / Eastern